An Option for Lemons? The Fair Value Option for Liabilities During the Financial Crisis. (October 2016) - Wu, Wei; Thibodeau, Nicole; Couch, Robert
We test for the presence of adverse selection among firms adopting the fair value option for liabilities (FVOL) embedded in Statement of Financial Accounting Standards (SFAS) 159 during the financial crisis. The FVOL is a controversial accounting choice because it allows firms to increase earnings when credit quality deteriorates. We find that firms with higher credit risk, lower profitability, and negative abnormal stock returns are more likely to adopt the FVOL, and that these firms exhibit negative abnormal stock returns over 1- to 3-year horizons after adoption. We conclude that adverse selection occurs among adopters. Although these findings suggest that the FVOL reduces comparability and information transparency, they also imply that accounting choice can be a valuable tool for standard setting because it can induce firms to reveal their type.